Unemployment Management Strategy Policy Secondary Education Graduates In Banten Province - Taufiqurokhman Taufiqurokhman (Universitas Sultan Ageng Tirtayasa, 2025)
Banten Province has the highest Open Unemployment Rate (TPT) for Vocational High School (SMK) graduates in Indonesia, becoming a serious concern in the world of education and employment. This study aims to analyze the policy strategy for overcoming unemployment for SMK graduates in Banten Province. Using a qualitative method with a descriptive design, data was obtained through interviews and documentation studies from various sources with a purposive sampling technique. The research locus covers 8 districts/cities in Banten with a sample of 80 informants from state and private SMKs. The results of the study show that the five majors that are most absorbed by the business world and industry (DUDI), namely informatics engineering, automotive engineering, graphic design, accounting, and health. The three main factors causing the high TPT of SMK graduates are limited productive teachers, suboptimal education quality, and the mindset of students who are only ready to work without relevant skills readiness. The policy gap can be seen from the lack of integration between vocational education policies and the real needs of DUDI in the regions. Recommendations include formulating policies for vocational schools based on superior vocational skills, equalizing vocational schools across all sub-districts, and strengthening graduates' soft skills and hard skills that are relevant to industry needs.